Diseño organizacional y gestión del talento humano en el hotel Floy´s International de la ciudad de Loja. - Quille Naranjo, Segundo Fernando (2012)
Today we are living in the era of globalization, in which each day is required of professionals with greater specialization and expertise, and which recognizes human resources as the key factor leading to the achievement of high levels of efficiency and effectiveness, Here comes the importance of establishing clear routing measures that lead to achievement of these objectives, requiring time, knowledge and application of tools for effective personnel management, any company whether this large, medium or small needs good resources for to perform their activities. Today technology is essential to the productivity demanded by the market, but the success of any enterprise depends largely on the flexibility and innovative capacity that has the personnel working in the organization, the only competitive advantage that can differentiate one company from another is the ability of staff to adapt to change, for which we must attract the best human capital, help them develop professionally retain them, give them the tools to make them more efficient and above all establish good organizational designs enable them to develop their activities efficiently, evaluate it by train, work properly design, setting appropriate goals, motivate, reward, so workers will be engaged and so will their potential to develop their activities within the company. Every company should establish an appropriate organizational design that lets you define its structure and to better relate to the employee with the position he will play. This thesis, aims to raise awareness of the relevant aspects of a company to provide solutions and improve the activities of the same, this is what took place starting from a subject of study up to the respective recommendations given to each of the findings detect in it, serving as support for the company to improve its activities. This thesis is structured as follows: The issue that is the focus of the work to which he has structured and defined for the first point has been based content, classification and space needed to do and we define a resource base with which account for execution, called: "Organizational design and talent management FLOY'S INTERNATIONAL HOTEL CITY LOJA" The Introduction was made to start based on the importance of the issue for companies in general, where we started and how far we want to go quickly and detailing as the work was done step by step. The summary is a brief guideline of what the thesis contains the most essential to disclose in a clear and concise statement of what it is. The materials that were used to support the introduction and implementation of the project are: Computer, Flash memory, Ream boom sheets, stationery and literature. The literature review was conducted based on the collection and selection of information obtained from different literature sources. The methods used and that allowed us to better lead the development of the thesis project were the scientific, inductive, deductive, mathematical and historical, as these were supplemented with different research techniques such as observation, interviews and surveys that served to obtain more real and see the reality of "Floy's International Hotel of the city of Loja" company under study, without leaving aside the population was made up of all the staff, with a total of eleven people. The results is the information obtained from the interview which was conducted by his manager-owner and the survey of employees, whose information was tabulated, with the corresponding graphical representation, analysis and interpretation. And some questions that helped us to make the identification of the position. The discussion is proposed based on the objectives and the information obtained, to be applied to improve the performance and development of the company, after a diagnosis is seen fit to propose: an organizational design comprised of: organizational structural, functional and positional, operating manuals, stage intake staff, training and motivation of this valuation followed by quality and performance evaluation this will help for a better development in the company. As a point following the presentation of conclusions made their respective recommendations were determined based on the information collected and analyzed in order to provide better development of "Floy's International Hotel of the City of Loja". As the literature endpoints are where you find the different sources of information for supporting the theoretical framework of the annexes have been located interview formats, the survey and the photo of the outside of the company and finally is the index which lists the points that make up the pages with their respective research.